(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In the mining field IOT has a great importance with varying applications drawing attention to its construction. To the contrary side the main objective of this research is to design smart helmet system for mining industry application which would be monitored by the system on the grounds of hazardous events such as temperature, humidity, gas, removal helmet of the miner and obstacle damage to the helmet. IOT based mining tracking and safety helmet made the working of the workers in the mining field much easier as compared that to the past decades. Detecting the upcoming challenges in the surrounding areas of the mines under suitable circumstances over the past few decades it helped the workers working in the mining field to come up with various solutions in a matter of time which caused a huge advantage during the work.